2003
DOI: 10.1111/j.1749-6632.2003.tb03152.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neural Inflammation in Asthma and Chronic Obstructive Pulmonary Disease

Abstract: The tachykinins substance P and neurokinin A are found within airway nerves and immune cells. They have various effects on the airways that can contribute to the changes observed in asthma and chronic obstructive pulmonary disease. Both tachykinin NK(1) and NK(2) receptors have been involved in the bronchoconstriction and the proinflammatory changes induced by substance P and neurokinin A. Tachykinin NK(1) and NK(2) receptor antagonists have activity in various animal models of allergic asthma and chronic bron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 87 publications
(107 reference statements)
0
25
0
Order By: Relevance
“…The assumption is that these events trigger and up-regulate an NK-1-dependent pathway, leading to increases in ACh release. The role of NK receptors and their agonistic tachykinins in allergic airway inflammation is somewhat controversial (37). In a recent study, Boot and colleagues demonstrated that a NK1/ NK2 dual antagonist failed to modulate AHR and airway inflammation after allergen challenge in patients with asthma (38).…”
Section: Discussionmentioning
confidence: 99%
“…The assumption is that these events trigger and up-regulate an NK-1-dependent pathway, leading to increases in ACh release. The role of NK receptors and their agonistic tachykinins in allergic airway inflammation is somewhat controversial (37). In a recent study, Boot and colleagues demonstrated that a NK1/ NK2 dual antagonist failed to modulate AHR and airway inflammation after allergen challenge in patients with asthma (38).…”
Section: Discussionmentioning
confidence: 99%
“…The release into the airways of tachykinins and neurokinins and the decrease of β 2 -adrenergic receptor, cholinesterase and neutral endopeptidase activities have been documented in these experimental conditions [3][4][5][6][7]60]. Conversely, reducing agents exert a relaxing effect on airway smooth muscle and they can inhibit bronchial smooth muscle contraction and prevent airway hyperresponsiveness in several experimental models [3][4][5][6][7]61].…”
Section: Asthmamentioning
confidence: 94%
“…The mechanisms, including both allergic pathways (adaptive immunity) and nonallergic (innate) pathways, are implicated in asthma and contribute to the complexity of this disease (77). Therefore, the development of relevant models to study the mechanisms leading to the development of asthma is a great challenge (26,69). Current models mainly use allergic airway disease as an alternative for asthma, and many models are based on short-term, acute exposures to simple protein antigens, microorganisms, or chemical compounds (5).…”
Section: Chemokine Receptors In Chronic Lung Diseasesmentioning
confidence: 99%